Spreading the cult body on YouTube: A case study of "Telephone" derivative videos - Agnese Vellar (Transformative Works and Cultures, 2012)
This case study of spreadability analyzes the Lady Gaga music video "Telephone," which has been appropriated and reworked by YouTube users sharing derivative works online. What properties of the music video stimulate user appropriation? What hybrid audiovisual forms are emerging from its reworking by users? In order to answer these questions, between January and August 2010, I conducted participant observation on Lady Gaga's official social network profiles and collected 70 "Telephone" derivative videos on YouTube. I identified three main categories of video creativity: (1) music (which includes covers, "me singing" videos, music mashups, and choreography); (2) parody (in which YouTube users and comedians humorously imitate Gaga, creating spoofs); and (3) fashion (in which makeup artists and amateurs appropriate the star's image to create makeup and hair tutorials). "Telephone" has become spreadable because it integrates dance music and choreography, costume changes, cinematic references, and product placements that work as textual hooks meaningful to different target markets: live music, dance, chick, and postmodern cinematic cultures. In particular, Gaga is a cult body that explicitly incorporates previous cinematic and pop music icons. Users are stimulated to reenact Gaga's cult body online. On YouTube, spreadability is thus strictly related to the appropriation of cult bodies. Fans, comedians, independent musicians, fashionistas, and pop stars construct their own cult bodies by deliberately borrowing characteristics from previous media icons and reenacting them in online videos in order to fulfill their expressive and professional needs.